The Influence of 1 on 1 Games on the Ball Dribbling Ability of Students at MTs Nurul Cholil 03 - Shaleh, Bani; Purwoto, Septyaningrum Putri; Widodo, Haryo Mukti; Sumroti, Nuning Aisyah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical education plays an important role in improving students' motor skills and fitness. One important aspect of playing football is a dribbling technique, which requires good coordination, balance, and control. However, many students still have difficulty dribbling the ball properly. Therefore, this study aims to analyze the effect of one-on-one games on improving students' dribbling skills at MTs Nurul Cholil 03. The purpose of this study was to determine the effect of one-on-one games on dribbling skills in students at MTs Nurul Cholil 03. This study used a quantitative method with a pre-experimental experimental approach (pretest-posttest design). The sample used was 20 students from classes VII A and VIII A who had difficulty dribbling the ball. Data collection techniques were carried out through observation, documentation, and dribbling skills tests before and after treatment. Data were analyzed using the Shapiro-Wilk normality test and hypothesis testing with paired t-tests using SPSS 20 software. The results of the normality test showed that the pretest and posttest data were normally distributed. Hypothesis testing shows a significance value of 0.005 <0.05, which means that there is a significant effect of one-on-one games on students' dribbling ability. After the treatment was given, students showed an increase in ball control, balance, and dribbling strategy, compared to the pretest results before the treatment. One-on-one games have proven to be effective in improving students' dribbling ability. With training that focuses on individual skills, students are able to develop better techniques in carrying the ball and defending the ball from opponents. Therefore, this method can be used as an alternative learning method to improve football skills in physical education.